1999
DOI: 10.1128/aac.43.7.1549
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of the Effect of an Aminoglycoside Dosing Regimen on Rates of Observed Nephrotoxicity and Ototoxicity

Abstract: The nephrotoxicity and ototoxicity associated with once-daily versus twice-daily administration of aminoglycosides was assessed in patients with suspected or proven gram-negative bacterial infections in a randomized, double-blind clinical trial. Patients who received therapy for ≥72 h were evaluated for toxicity. Patients also received concomitant antibiotics as deemed necessary for treatment of their infection. Plasma aminoglycoside concentrations, prospective aminoglycoside dosage adjustment, and serial audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
168
2
8

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(186 citation statements)
references
References 43 publications
7
168
2
8
Order By: Relevance
“…Reported nephrotoxicity of aminoglycosides dosed once daily varies between 0-5% [26,27], while this occurs in up to 17% in multiple dosing [27]. Assessment of nephrotoxicity of aminoglycosides in ICU patients is hampered by the presence of numerous other risk-factors, such as hypotension and the concomitant use of other nephrotoxic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Reported nephrotoxicity of aminoglycosides dosed once daily varies between 0-5% [26,27], while this occurs in up to 17% in multiple dosing [27]. Assessment of nephrotoxicity of aminoglycosides in ICU patients is hampered by the presence of numerous other risk-factors, such as hypotension and the concomitant use of other nephrotoxic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors may include duration of therapy and magnitude of peak drug concentrations in the context of divided daily therapy [5]. In contrast, single-dose daily aminoglycoside therapy may reduce the incidence of renal dysfunction [6]. The mechanism for aminoglycoside uptake into proximal tubular cells is saturable, and thus, giving the total daily dose at one time may reduce cellular accumulation [7].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for aminoglycoside uptake into proximal tubular cells is saturable, and thus, giving the total daily dose at one time may reduce cellular accumulation [7]. However, once-daily dosing does not change aminoglycoside-associated ototoxicity [6]. In addition, peak levels greater than 40 mg/L have rarely been reported [8].…”
Section: Discussionmentioning
confidence: 99%
“…In view of its concentration-dependent killing, the peak drug concentration in relation to the minimum inhibitory concentration (MIC) ratio for aminoglycosides has been repeatedly shown to be the PK/PD parameter most closely linked to bacterial killing against gram-negative bacteria. Some clinical trials demonstrated a small but significant benefit in clinical outcomes with once-daily dosing [3], whereas other studies demonstrated that the once-daily regimens significantly delayed the onset of nephrotoxicity compared to twice-daily and thrice-daily administration [4,5]. As a result, almost 75% of US hospitals have adopted the extended-interval aminoglycoside dosing, and usage among all age groups has increased [6].…”
Section: Introductionmentioning
confidence: 97%